2013
DOI: 10.1007/s00221-013-3745-4
|View full text |Cite
|
Sign up to set email alerts
|

Haptic two-dimensional angle categorization and discrimination

Abstract: This study examined the extent to which haptic perception of two-dimensional (2-D) shape is modified by the design of the perceptual task (single-interval categorization vs. two-interval discrimination), the orientation of the angles in space (oblique vs. horizontal), and the exploration strategy (one or two passes over the angle). Subjects (n = 12) explored 2-D angles using the index finger of the outstretched arm. In the categorization task, subjects scanned individual angles, categorizing each as "large" or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In this paradigm, we used the two-angle discrimination method from previous studies to measure the angle DT for the participants. Seven different angles (20 • , 22 • , 24 • , 26 • , 28 • , 30 • and 32 • ) were used in the comparison discrimination of the two angles [12,18,26,27]. In the experiment, one of seven angles was used as the standard angle (SA), and the other six angles were used as the CAs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paradigm, we used the two-angle discrimination method from previous studies to measure the angle DT for the participants. Seven different angles (20 • , 22 • , 24 • , 26 • , 28 • , 30 • and 32 • ) were used in the comparison discrimination of the two angles [12,18,26,27]. In the experiment, one of seven angles was used as the standard angle (SA), and the other six angles were used as the CAs.…”
Section: Methodsmentioning
confidence: 99%
“…In some previous studies, stimuli of two-dimensional (2-D) raised-line drawings were used to explore the touch perception process [24][25][26][27]. The accuracy of 2-D raised-line…”
Section: Haptic Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans' ability to perceive angle and length properties of an object through touch has been demonstrated repeatedly (e.g., Hollins & Goble, 1988;Shimizu & Norimatsu, 2005;Toderita, Bourgeon, Voisin, & Chapman, 2014;Voisin, Benoit, & Chapman, 2002). In contrast, only two studies have reported that blindfolded adults could spontaneously use length cues to locate using touch (Sturz, Gaskin, & Roberts, 2014;Sturz, Green, et al, 2013a), and no evidence exists on the role of angles.…”
Section: Introductionmentioning
confidence: 99%